New Spectrophotometric Methods for the Determination of Fluatamide - Reddy, M.N.; Murthy, T.K.; Rajita, K.; Dharma Reddy, M.; Shankar, D.G. (Asian Journal of Chemistry, 2010)
Two simple, sensitive and reproducible spectrophotometric methods (Method A and Method B) are developed for the determination of flutarnide in pure and dosage forms. These methods are based on the formation of coloured species on treatment of reduced flutamide with p-dimethyl aminocinnamaldehyde [Method A) and diazotization followed by coupling with N-1-naphthyl ethylene diamine dihydrothloride (BM reagent) [Method B).